Financial constraints and the margins of FDI - Claudia M. Buch; Iris Kesternich; Alexander Lipponer; Monika Schnitzer (Deutsche Bundesbank, 2009)
Recent literature on multinational firms has stressed the importance of low productivity as a barrier to the cross-border expansion of firms. But firms may also need external finance to shoulder the costs of entering foreign markets. We develop a model of multinational firms facing real and financial barriers to foreign direct investment (FDI), and we analyze their impact on the FDI decision (the extensive margin) and foreign affiliate sales (the intensive margin). We provide empirical evidence based on a detailed dataset of German multinationals which contains information on parent-level and affiliate-level financial constraints as well as about the location the foreign affiliates. We find that financial factors constrain firms' foreign investment decisions, an effect felt in particular by large firms. Financial constraints at the parent level matter for the extensive, but less so for the intensive margin. For the intensive margin, financial constraints at the affiliate level are relatively more important.
Keywords: F2; G2; 330; Multinational firms; heterogeneity; productivity; financial constraints